How Democracy Works : Political Representation and Policy Congruence in Modern Societies. - Rosema, Martin (Amsterdam University Press, 2011)
This book analyses the functioning of modern democracies in terms of two basic principles: political representation and policy congruence between citizens and their representatives. Fundamental changes in society have challenged democracy's functioning and this book examines whether democracy still works today, and, if so, how it works. They present new insights into the mechanisms that create policy congruence, the sources of satisfaction with democracy, and the role of the economy in holding governments accountable. The authors utilize recent survey data from a variety of national and intern.